(untitled) (Itinera, 2013)
It is known that posdtdramatic objects are difficult to study because of the importance they give to lived material experience. One doesn’t know what elements are to be chosen and if they will be significant, nor which method should be used to avoid blasting them away with an analysis which would most certainly dissect and decompose them in a lifeless body. They actually raise unprecedented esthetic as well as analytic problems, which make them even more fascinating to the researcher.